2017
DOI: 10.1111/ggi.13164
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment has no impact on hospital‐associated dysphagia in aspiration pneumonia patients

Abstract: The severity of cognitive impairment has no impact on hospital-associated dysphagia in AP patients receiving dysphagia rehabilitation. A future interventional study will be expected to further validate our findings. Geriatr Gerontol Int 2018; 18: 233-239.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 28 publications
(34 reference statements)
2
13
2
1
Order By: Relevance
“…however, those with head and neck cancer tended to exhibit poor FOIS scores, which was consistent with the ndings of previous studies [30,31]. satisfaction, type of housing, number of cohabitants, and perceived satisfaction with social support) and dental status [32][33][34][35][36][37].…”
Section: Generalizability From the Demographic Datasupporting
confidence: 88%
“…however, those with head and neck cancer tended to exhibit poor FOIS scores, which was consistent with the ndings of previous studies [30,31]. satisfaction, type of housing, number of cohabitants, and perceived satisfaction with social support) and dental status [32][33][34][35][36][37].…”
Section: Generalizability From the Demographic Datasupporting
confidence: 88%
“…Activity-and nutrition-related unfavorable conditions were independently associated with swallowing disorder development, and in the subgroup analysis, the simplified diagnosis of sarcopenia also predicted the development of such a condition. The results indicated that hospital-associated dysphagia, referring to a swallowing disorder acquired during hospitalization [13], mostly seemed to be sarcopenic dysphagia. A previous study investigating older inpatients with were prohibited oral ingestion at admission to the hospital reported that only patients with sarcopenia developed swallowing disorders within two months, and lower muscle mass and poorer physical function were the predictors of sarcopenic dysphagia [12].…”
Section: Discussionmentioning
confidence: 96%
“…Hospitalization may accelerate the development of sarcopenic dysphagia, which is a swallowing disorder due to sarcopenia [13]. Several studies have reported that hospitalization reduces the muscle mass and strength of older inpatients [14,15], which could have resulted from insufficient nutrition, forced bedrest, and the presence of diseases causing sarcopenia during hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…Nine studies used the Mini‐Mental Status Examination (MMSE) to assess cognitive disorder, 7,10,16–22 and one study used the Montreal Cognitive Assessment 6 …”
Section: Resultsmentioning
confidence: 99%